2021
DOI: 10.1016/j.psj.2021.101068
|View full text |Cite
|
Sign up to set email alerts
|

The influence of feed ingredients on CP and starch disappearance rate in complex diets for broiler chickens

Abstract: The influence of feed ingredients on digestion kinetics of N and starch in complex diets was investigated in the current experiment. A total of 34 diets with different inclusion levels of 10 commonly used feed ingredients (corn, wheat, sorghum, soybean meal, canola meal, full-fat soybean meal [ FFSB ], palm kernel meal, meat and bone meal, wheat distillers grain with solubles and wheat bran) were randomly allocated to 170 cages with 8 birds in each. Apparent jejunal and ileal digestibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Conversely, slowly digestible starch would make more glucose available in the posterior small intestine to be oxidized, again potentially sparing amino acids from catabolism. The importance of understanding kinetics of digestion and its complexity was emphasised in a recent, comprehensive study reported by Pedersen et al [ 165 ].…”
Section: Starch-protein Digestive Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, slowly digestible starch would make more glucose available in the posterior small intestine to be oxidized, again potentially sparing amino acids from catabolism. The importance of understanding kinetics of digestion and its complexity was emphasised in a recent, comprehensive study reported by Pedersen et al [ 165 ].…”
Section: Starch-protein Digestive Dynamicsmentioning
confidence: 99%
“… Quadratic relationship ( r = 0.634; p < 0.005) between starch digestion rate constants and FCR where: y = 5.470 − 2.431 x starch + 0.367 x starch 2 from 7 to 35 days post-hatch [ 165 ]. …”
Section: Figurementioning
confidence: 99%
“…Los resultados indican que los niveles de sustitución parcial o total de la dieta finalizadora por maíz amarillo en pollos criollos generaron diferentes pesos finales e índices de conversión alimenticia. Similares hallazgos se determinaron en pollos de engorde cuando variaron las cantidades ingeridas de cada ingrediente y los nutrientes alimenticios, atribuyéndose la variación del rendimiento a la influencia de los niveles de ingesta de los nutrientes de un determinado ingrediente sobre la tasa de desaparición de los nutrientes de los demás ingredientes de la dieta (Pedersen et al, 2021). Esto destaca la importancia de comprender la cinética de la digestión de nutrientes y cómo estos se ven influenciados, tanto de forma aditiva como no aditiva, por los ingredientes del alimento (Selle y Liu, 2019).…”
Section: Resultados Y Discusión Rendimiento Productivounclassified
“…The incorporation of amino acids into protein, or protein accretion, is dependent on the harmonious availability of the appropriate blend of amino acids and the provision of energy (derived mainly from glucose) at sites of protein synthesis [57,58]. As implied, the digestion dynamics of protein/amino acids should not be considered in isolation from those of starch/glucose because of the interactions that take place in broiler chickens offered practical diets [59]; nevertheless, the focus of this review is the bioequivalence of amino acids.…”
Section: Digestive Dynamics Of Amino Acidsmentioning
confidence: 99%